REPRODUCIBILITY AND EQUIVALENCE OF COBBMETER APPLICATION IN THE SAGITTAL EVALUATION OF THE SPINE - Marchi,Luis (2016)
ABSTRACT Objective: This study aims to evaluate the reliability and equivalency of using the Cobbmeter application for iPhone compared to the manual measurement method in the analysis of the sagittal spinal alignment. Methods: Cross-sectional, prospective, single-center study that had 20 panoramic radiographs of the spine in lateral view, in a neutral standing position, analyzed blindly and randomly by three independent examiners in three different times. The parameters were pelvic incidence (PI), pelvic tilt (PT) and lumbar lordosis (LL). The statistical analysis was performed to measure the intraclass correlation coefficient (ICC) between the two measurement methods, in addition to measuring the intra and inter-evaluators reliability. Results: For reproducibility analysis, the intra-evaluators ICC using the application resulted in a Kappa (K) of 0.975 for the evaluation of pelvic incidence (PI) evaluation. For pelvic tilt (PT), the K value obtained was 0.981 and the K measured for lumbar lordosis (LL) analysis was 0.987. The inter-evaluators evaluation of reproducibility using the application resulted in a K value of 0.917 for PI, 0.930 for PT and 0.951 for LL. For the assessment of equivalency of methods, comparing the application to the standard method, with a goniometer and dermographic pencil, the K value found for PI was 0.873, for PV was 0.939 and for LL was 0.914. All values were significant (p<0.001) against the null hypothesis. Conclusion: This smartphone application is a valid and reliable instrument for measuring the angle involved in the sagittal balance of the spine. Furthermore, the results show that its applicability is not inferior to the manual method with goniometer and dermographic pencil.